IL-10, IL-12B and IL-17 gene polymorphisms in patients with mixed connective tissue disease. Issue 3 (May 2015) - Paradowska-Gorycka, Agnieszka; Jurkowska, Monika; Czuszynska, Zenobia; Felis-Giemza, Anna; Mańczak, Malgorzata; Zdrojewski, Zbigniew; Olesinska, Marzena
Abstract Objectives. Mixed connective tissue disease (MCTD) is a rare systemic autoimmune disease with a prevalence of about 10 cases/100, 000. It seems that in the pathogenesis of MCTD no individual cytokines/cells, but rather an altered pattern of these markers altogether may contribute to the autoimmune processes and their balance determines disease activity. IL-10, IL-12 and IL-17F as inflammatory cytokines might be an important functional candidate genes for autoimmune diseases including MCTD. Methods. The study group consisted of 66 patients with MCTD and of 106 (163 for IL-12B) healthy individuals. SNPs in the IL-10 (− 592C/A, − 1082G/A), IL-12B (+ 1188A/C) and IL-17F (His161Arg, Glu126Gly) genes were investigated by PCR-RFLP approach. Results. The frequency of the IL-10-592A and -1082A allele was higher in MCTD patients than in control groups (both p = 0, 0000). In addition the -1082G/A IL-10 gene polymorphism was associated with esophageal involvement and with anti-U1-A and –C antibodies. The IL-17 7488A/G variant showed correlation with presence of anti-SmB and anti-dsDNA antibodies, while the IL-17F 7383A/G variant was associated with Sjögren's syndrome and leuco-and thrombocytopenia. Moreover, the IL-12 SNP + 1188A/C showed correlation with sclerodactyly in MCTD patients. Conclusion. Present findings indicate that IL-10 gene variants may be considered as genetic risk factors for MCTD susceptibility.